2018
DOI: 10.1038/gim.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic heterogeneity in a large cohort of Armenian patients with late-onset familial Mediterranean fever

Abstract: PurposeThis work aimed at investigating demographic, clinical, and genetic characteristics of individuals experiencing their first familial Mediterranean fever (FMF) attack at age ≥40 years in a very large cohort of Armenian FMF patients.MethodsIn total, 10,370 Armenian patients diagnosed with FMF based on the Tel Hashomer criteria and carrying at least one MEFV mutant allele were included in this study.ResultsA total of 354 (3.40%) patients had late-onset FMF. Of these, 194 (54.80%) were female and 160 (45.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
2
7
1
Order By: Relevance
“…In a study by Ureten et al comparing M694V homozygous, heterozygous and other mutations, disease onset was found to be lower in relative order (12). Similar findings were presented in other studies (13,14,16). Our results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…In a study by Ureten et al comparing M694V homozygous, heterozygous and other mutations, disease onset was found to be lower in relative order (12). Similar findings were presented in other studies (13,14,16). Our results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…In a study by Ureten et al comparing M694V homozygous, heterozygous and other mutations, disease onset was found to be lower in relative order (12). Similar ndings were presented in other studies (13,14,16). Our results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 78%
“…Fever was also found to be more frequent in patients with disease onset before 40 years when compared to after 40 years in the study of Tamir et al (13). In an Armenian cohort with 10370 patients, fever was also found to be more frequent with earlier onset (14). Nevertheless, fever was also found to be the most common second symptom in group 1.…”
Section: Discussionmentioning
confidence: 82%
“…Approximately 90% of FMF patients experience their first attack before the age of 20 (37). FMF with the first attack at age ≥ 40 years is rare and there are only a few studies investigating the clinical and molecular genetic characteristics of late-onset FMF patients [38][39][40]. There is no definitively accepted age limit for late-onset FMF disease.…”
Section: Clinical Features Of Familial Mediterranean Fever By Age And...mentioning
confidence: 99%
“…There is no definitively accepted age limit for late-onset FMF disease. In some studies, this limit is >20 years old, while in others it is ≥40 years old (38)(39)(40)(41). Tamir et al examined FMF patients whose attacks of FMF started after the age of 40 and showed that they had a milder disease course.…”
Section: Clinical Features Of Familial Mediterranean Fever By Age And...mentioning
confidence: 99%